Perancangan dan Implementasi Aplikasi Manajemen Absensi Berbasis Mobile Menggunakan Flutter dan Laravel - Sunarsa, Teofilus; Novaliansyah, Syawaludin (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
Manual attendance systems are still widely used in educational institutions and companies, leading toinefficiencies in recording, monitoring, and reporting attendance. This study aims to design and implement amobile-based attendance management application using Flutter as the frontend and Laravel as the backend. Thedevelopment method used is the Waterfall model with stages of needs analysis, system design, implementation,and testing. The application is equipped with login features, user data management, digital attendancerecording, and attendance reports accessible via smartphones. Functional testing results show that all featureswork as expected. Integration between Flutter and Laravel through RESTful API proves effective in supportingstable and secure data communication. With this application, the attendance process becomes more efficient,structured, and easy to monitor.